Generations at a Glance - Megan S. Cantrell (EDIS)
Generational differences are a topic that has been discussed for decades, and interest in it is increasing in the 2020s as people are finding jobs younger and retiring older than ever before in American history. Five generations, from Traditionalists through Generation Z, are engaged in the workforce as consumers, employers, and managers. This new 4-page publication, written by Megan S. Cantrell, provides an overview of the influences and notable qualities of these generations. https://edis.ifas.ufl.edu/wc398